THE NEED FOR SRATEGY IN THE TRAINING OF EMPLOYEES: A CONDITION FOR IMPROVING THE HUMAN CAPITAL IN ROMANIA, AS EU MEMBER - Roxana-Manuela, DICU; Daniela-Neonila, MARDIROS (Strategii Manageriale, 2014)
As a component of the intellectual capital, the human factor is a competitive resource, full of potential and economic benefits. The use of it should be further promoted, while improving the consistency of definitions and methods across Europe. Knowing the fact that the business environment is based on the human capital, it should also take into account the views of stakeholders and the developments in accounting rules and corporate governance in order to assess, to measure and to report this component of intellectual capital. Of course, for Romania, being a part of the huge mechanism that is EU means a new perspective for the use of human capital and for the understanding of its importance. The main focus of the paper is on Romania's strategy regarding human capital, which should be consistent with EU 2020 Strategy, should be based on the idea that intellectual capital investments and assets are necessary, but not sufficient to make human capital productive, and a change of perspective is necessary.